Young people in Europe : labour markets and citizenship - Bradley, Harriet; Hoof, J. J. B. M. van (Policy Press, 2005)
In a period of rapid social and economic change, labour markets are undergoing major transformations. This book explores the changing fortunes of young people in Europe's flexible and precarious labour markets and the range of policies that are being developed to help them deal with the problems they face.